Traffic regulations : DOI: 10.5937/etp2503035M - Mitrić, Vidoje (Ekonomija - teorija i praksa, 2025)
The main goal of this research is to analyze regulations in the field of traffic, with a special focus on road traffic, in order to understand their role in improving the safety, efficiency, and sustainability of the traffic system. Road traffic represents one of the most important segments of the transport system, and therefore legal frameworks and regulations are essential for its functioning. Regulations in this area include laws, rulebooks, and standards that define technical requirements for vehicles, traffic regulation on roads, the rights and obligations of traffic participants, as well as measures for preventing and sanctioning violations. Special emphasis is placed on the Law on Road Traffic Safety, which represents the fundamental legal framework for regulating this field. The aim of this research is to highlight the importance of harmonizing national regulations with international standards, as well as the need for continuous adaptation of the legal framework to respond to the challenges of modern traffic. The effects of the implementation of these regulations on reducing traffic accidents and improving the quality of road traffic will also be analyzed.